The impact of age on female body posture - Agnieszka Jankowicz-Szymańska; Marta Bibro; Katarzyna Wódka; Eliza Smoła (University of Applied Sciences in Tarnow, Poland, 2018)
Introduction and aim of the study: The body posture, which is one of the determinants of health and functional efficiency, changes depending on gender, age and psychophysical condition. Defining a pattern of correct posture is extremely difficult as it is a highly individualised feature. The aim of this paper was to compare the body posture of women in three periods of ontogenesis: girls in puberty, young adult women and women in the geriatric age. Material and methods: 150 women were examined: 50 12-year-old pupils, 50 20-22-year-old students and 50 women aged 60-84. Their height and weight were measured, BMI calculated and the status of body weight determined as normal, overweight or obese. The Zebris Pointer ultrasound system analyzed the position of the spine in the sagittal and frontal plane, the symmetry of the shoulders and pelvis in the frontal plane, and the balance of the torso in the sagittal and frontal plane. The results were developed with the Statistica programme. Basic descriptive statistics, multiplicity tables, Shapiro-Wilk test (study of normality of distribution) and Kruskal-Wallis test (inter-group comparison) were used. Differences between groups were assumed to be significant when p<0.05. Results: Age significantly differentiated the BMI index of the surveyed. Overweight and obesity was more prevalent in the oldest age group. The size of thoracic kyphosis expressed in degrees was similar in all the surveyed, although hypokyphosis was observed more frequently in the female pupils and hyperkyphosis in the female students. Lumbar lordosis was significantly higher in the students when compared to the other groups. Hypolordosis was most common in the seniors. The students and seniors also differed in terms of the balance of the torso in the sagittal plane. Excessive backward inclination was diagnosed in 42% of the students (total backward shift of the centre of gravity of the human body), which was twice as rare in the female students and four times as rare in the seniors. Asymmetric position of the right and left shoulder and hip girdles was common in every group of the women surveyed. Side bendings of the spine were most often observed in the female pupils, and least frequently in the seniors. Left-sided bendings were more frequent than right-sided ones. Conclusions: The age of women affects the position of the torso more in the sagittal plane than in the frontal one. The size of lumbar lordosis is an element of the body posture most significantly differentiating women between 12 and 84 years of age. Hyperlordosis is more characteristic of young adult women, whereas hypolordosis of seniors. Hyperkyphosis is most common in female students while hypokyphosis in adolescent girls.